2011
DOI: 10.1007/s00264-011-1246-2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial lengthening over an intramedullary nail in patients with short stature or leg-length discrepancy: a comparative study

Abstract: Purpose The aim of this study was to review our experiences with tibial lengthening over an intramedullary nail in comparison to the conventional Ilizarov method. Methods We performed a retrospective comparison of tibial lengthening using the conventional Ilizarov method (group A: 23 limbs in 13 patients) versus over a nail (group B: 51 limbs in 26 patients). The percentage increase in tibial length, lengthening index, external fixation index, consolidation index and complications were assessed. Results The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 16 publications
2
31
0
2
Order By: Relevance
“…However, the concomitant use of an intramedullary nail, such as with tibial LON, can act as a strong resistance to the deforming forces, minimizing axial deviations compared with the classic Ilizarov method. Some studies [2,3,15,20,21] compared the classic Ilizarov method with the LON technique and showed that axial deviation occurred in 4% to 13% of tibias with the classic Ilizarov method, whereas it was 0% to 2% with the LON technique. However, Kim et al [8] reported that they observed 20 segments (14%) that showed valgus angulation with a mean of 10°using the LON technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the concomitant use of an intramedullary nail, such as with tibial LON, can act as a strong resistance to the deforming forces, minimizing axial deviations compared with the classic Ilizarov method. Some studies [2,3,15,20,21] compared the classic Ilizarov method with the LON technique and showed that axial deviation occurred in 4% to 13% of tibias with the classic Ilizarov method, whereas it was 0% to 2% with the LON technique. However, Kim et al [8] reported that they observed 20 segments (14%) that showed valgus angulation with a mean of 10°using the LON technique.…”
Section: Discussionmentioning
confidence: 99%
“…It can act as a guide such that the bone is lengthened along the longitudinal axis of the nail with no axial deviations. It was reported that the secondary deformity induced during distraction could be substantively negated with the intramedullary nail in the LON technique of the tibia [3,15,20,21]. However, Kim et al [8] reported that a valgus deviation was the most common complication in 20 segments (25%) in their series of the LON technique of the tibia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined techniques resulted in the reduction of the usual IEF duration and good union rates [35]. There were many clinical studies of using the external fixator over the nail or FIN for orthopaedic conditions and injuries [4, 5, 11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…They are reported after failed total knee arthroplasty (TKA), severe post-traumatic osteoarthritis in young patients, reconstruction after tumor resection, chronic sepsis and totally destroyed knee joints after severe trauma [1][2][3]. Using this technique the intramedullary nail prevents bending, refracture [4][5][6][7], subsidence [8], bowing of the regenerate bone and secondary shortening. Furthermore the time in an external frame is shortened and improves patient´s comfort and life quality during the healing phase [9].…”
Section: Introductionmentioning
confidence: 99%